Malignant hyperthermia in the early days of pediatric anesthesia: an interview with anesthesiology pioneer, Dr. John F. Ryan. Issue 9 (3rd June 2015) - King, Michael R.; Firth, Paul G.; Yaster, Myron; Ahmed, Zulfiqar; Mai, Christine L.; Bosenberg, Adrian
Summary Dr. John F. Ryan (1935 ‐ ), Associate Professor of Anaesthesia at the Harvard Medical School, influenced the careers of hundreds of residents and fellows‐in‐training while instilling in them his core values of resilience, hard work, and integrity. His authoritative textbook, A Practice of Anesthesia for Infants and Children, remains as influential today as it did when first published decades ago. Although he had had many accomplishments, he identified his experiences caring for patients with malignant hyperthermia and characterizing the early discovery of this condition as his defining contribution to medicine. Based on a series of interviews with Dr. Ryan, this article reviews a remarkable career that coincides with the dawn of modern pediatric anesthetic practice.